Job Satisfaction of Paraprofessional Staff Working in Academic Libraries in Sri Lanka: A Case Study at the Library, University of Jaffna - Murugathas, K.; Santharooban, S. (University Librarians Association of Sri Lanka, 2025)
Paraprofessional staff in academic libraries play a vital role in providing efficient services to library readers. Their job satisfaction directly influences the quality of services offered by the library. This study explored the level of job satisfaction among the paraprofessional staff at the University of Jaffna Library and examined the main factors impacting their job satisfaction. Further, the study examined the influence of the selected demographic characteristics of the paraprofessional library staff members on their job satisfaction level. A survey research method was employed in this study. Self- administered pre-developed questionnaire served as the research tool for data collection. The total population of paraprofessional staff in this library was twenty-eight, all of whom were considered for the study. The collected data was analyzed using descriptive statistics and inferential statistics such as the Wilcoxon Signed Rank test, Kruskal-Wallis H test, and Mann-Whitney U. The survey evaluated various aspects of job satisfaction and how these different facets affect overall job satisfaction. Findings revealed that the study participants were moderately satisfied (x̄ = 3.12) with their current job. The facet ‘Nature of the Work’ received the highest satisfaction level, with a mean value of 3.61 (SD = 0.79). This was followed by ‘Supervision’ (x̄ = 3.50, SD = 0.48) and then ‘Coworkers’ (x̄ = 3.38, SD = 0.77). The lowest-scored facet (x̄= 2.64, SD = 0.50) was ‘Operating Procedures in the Library’. The facets ‘Rewards’, ‘Pay’, ‘Promotion’ ‘Opportunities’, and ‘Operating Procedures’ scored below the neutral mean value (3.00), suggesting dissatisfaction and requiring attention. The study identified a significant difference in ‘Pay’, ‘Benefits’, and ‘Rewards’ among different experience levels of the participants (p< 0.05). The analysis further revealed that other demographic factors, such as gender, age, and educational and professional qualifications, do not influence any of the assessed nine facets of job satisfaction (p>0.05) of the paraprofessionals working at University of Jaffna Library. The findings of the study would be helpful to administrators in identifying areas of concern and implementing strategies to enhance the job satisfaction of paraprofessional staff.
Keywords: Job satisfaction; Paraprofessional staff; University libraries; Sri Lanka; Academic libraries; Library Information Assistants